Peran Humas PT. Railink Dalam Memanfaatkan Media Sosial Sebagai Media Publisitas - Muhammad Hanif Muzhaffar; Samsul Bahri Pasaribu; Muhammad Haritz Arrasyid; Hasan Sazali (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Social media has become an essential part of daily activities, such as reading news, conducting buying and selling transactions, and various other activities. This has encouraged companies to have social media accounts to provide the latest information to the public. PT Railink has also adopted a similar strategy by utilizing its Instagram account, @kabandararailink, as a platform for disseminating information to the public. The presence of this account facilitates public access to the latest updates uploaded by the company. In this study, the author conducted observations and interviews to analyze the role of public relations as a publicity medium through PT Railink's Instagram account. The research method used is qualitative descriptive, aiming to understand how social media impacts companies, particularly PT Railink. The findings indicate that social media significantly influences the company, fostering reciprocal interaction between the public and the company. This study also highlights how PT Railink utilizes its Instagram account as a communication medium with the public. Instagram was chosen as the primary platform because it is one of the most frequently accessed social media platforms by the public and serves as a source of essential travel information, including travel requirements and departure schedules. This makes Instagram an effective tool for providing the public with the information they need.